Snakebite Envenomation From the Large Palearctic Viper, Macrovipera razii (Squamata: Serpentes; Viperidae), in Fars Province, Southern Iran - Saeed Shahabi; Kourosh Azizi; Aboozar Soltani; Azim Paksa; Mohammad Djaefar Moemenbellah-Fard; Mohsen Kalantari (Journal of Tropical Medicine)
Snakebites are a significant health issue, especially in tropical and subtropical regions. Envenomation from snakebites is a clinical emergency requiring prompt treatment. Recently, a new species of blunt-nosed viper, Macrovipera razii, was identified in central and southern Iran through morphological and molecular studies. This large, dangerous viper can deliver substantial amounts of venom. Following reports to the Faculty of Health at Shiraz University of Medical Science (SUMS), the identification of venomous snakes involved in envenomation cases in Fars province was undertaken. Approximately 20 snakes were captured and presented by locals, while others provided photos. Despite some information being photo-based, the data highlighted the significant role of this viper in envenomation cases. Macrovipera razii is now recorded from 12 counties in Fars province. One incident involved a male bitten in Shiraz, and another case led to a male needing limb amputation. This study emphasizes the importance of this newly described viper in recent snakebite envenomations in the region and reviews its distribution within the Fars province.